Prognostic implication and immunological value of contactin 1 expression in pan‐cancer - Lingyun Zhang; Jiayu Zhang; Tianshu Liu; Jinguo Zhang; Yuehong Cui (Wiley, 2022)
Abstract Objective Contactin 1 (CNTN1) is associated with developing the cancer progression and nervous system. Although increasing evidence suggests a crucial role for CNTN1 in many research areas, it is still no detailed systematic analysis of CNTN1 and the human pan‐cancer spectrum. Here, our purpose is to make a thorough investigation of CNTN1 properties across pan‐cancer types. Methods CNTN1 mRNA expression and genomic alteration were dissected by GTEX, TCGA, and the cBioPortal database. CNTN1 expression in human organic tissues was performed via human multiple organ tissue microarrays. Furthermore, the correlations between CNTN1 and survival periods, clinical characteristics, and immune‐associated cells infiltration were performed through the TCGA database. Additionally, GSEA was carried out to delve into the biological actions of CNTN1 in pan‐cancer. Results We discovered that CNTN1 expression was abnormal in pan‐cancer expression analysis and could predict the survival period of cancers. The primary alteration type of CNTN1 was a genomic mutation. In addition, the aberrant CNTN1 expression was found to be related to MSI, MMR, and TMB in pan‐cancer. CNTN1 was significantly related to the infiltration of immune‐associated cells in certain kinds of cancer through the ESTIMATE algorithm and TIMER database. In particular, the cancer‐associated fibroblasts indicate a negative regulation of the tumor immune microenvironment. Next, we found the most frequent signaling pathway of CNTN1 in human pan‐cancer was neuroactive ligand-receptor interaction from GSEA analysis. Conclusion In conclusion, the investigation highlights the predictive function of CNTN1 in human pan‐cancer and affords novel insights for drawing a landscape of CNTN1 in tumorigenesis and immune regulation.